OVERVIEW OF SELECTIVE COLLECTION FROM THE PERSPECTIVE OF THE ASSOCIATION OF RECYCLABLE MATERIAL COLLECTORS OF CÁCERES-MT – ASCARC - de Matos Sebalhos, Karen Mamoré; Sguarezi, Sandro Benedito; de Souza, Silvano Carmo; Souza, Erika Patrícia Lacerda Dias (Seven Editora, 2025)
The execution of Urban Solid Waste Management involves a complex process. Due to the fact that solid waste management is inherent to the municipality, each municipality establishes links with waste picker organizations in a different way. This paper analyzes, from the point of view of the ASCARC waste pickers, the limits and possibilities of the Cáceres Recicla Program, Municipal Law nº 2.367/2013, in relation to the socio-productive inclusion of recyclable material waste pickers. Waste pickers are important environmental agents and their perception of the processes that involve them contributes to the improvement of solid waste management, enabling solidary, more inclusive and efficient selective collection. Regarding the municipality of Cáceres-MT, it was observed that although ASCARC was the only organization qualified at the time of Public Call nº 001/2021, the associated waste pickers still lack training in relation to practices inherent to associated work, technical training and Environmental Education that allow the development of skills that lead them to critically analyze their important role within the municipality. These notes reflect directly on the importance of articulation between the municipal public management, educational institutions and organizations of waste pickers, in the sense that they are provided with adequate support for the execution of the selective collection service, as well as that they be able to provide information on the execution of the activity that provide subsidy for the elaboration of public policies, as well as their execution. DOI: https://doi.org/10.56238/sevened2025.029-045